Tender Rigging as a Violation of Competition Law : A Study of KPPU Decision No. 02/KPPU-L/2024 - Omar Damaraji Dewananda; Jeffri Marthan Leonard; Ibnu Zakaria (Universitas Muhammadiyah Surabaya, 2026)
Tender mechanisms are intended to ensure fair business competition; however, in practice, they are often manipulated through bid rigging that leads to unfair competition. This study examines the legal issue of how tender arrangements are classified as violations of competition law and analyzes the legal reasoning of the Business Competition Supervisory Commission (KPPU) in Decision No. 02/KPPU-L/2024. The purpose of this research is to analyze forms of tender arrangements that violate Law Number 5 of 1999 and to assess the legal considerations applied by the KPPU in deciding the case. This research employs normative legal research. The findings reveal that the tender arrangement in this case involved agreements among business actors and the participation of related parties, resulting in the elimination of fair competition, as evidenced by similarities in bid documents, predetermined tender winners, and actions that hindered other business actors from competing fairly. In its decision, the KPPU concluded that such conduct fulfilled the elements of bid rigging as stipulated in Article 22 of Law Number 5 of 1999, thereby legally and convincingly proving the occurrence of a violation of competition law. This decision affirms the role of the KPPU in enforcing fair competition principles and providing legal certainty in public procurement practices.